Biological carbon pump responses to multiscale physical processes: a review of sediment trap studies in the South China Sea - Zhang, Jingjing; Li, Hongliang; Wiesner, Martin G.; Ran, Lihua; He, Xingju; Chi, Guangxi; Wang, Xinyang; Yu, Jinping; Chen, Jianfang (Frontiers in Marine Science, 2023)
Accurately assessing the capacity of the modern ocean to photosynthetically fix and sequester atmospheric CO2, termed the biological carbon pump (BCP), is a key component in studies on the marine carbon cycle and the global climate system. Particulate organic carbon (POC) flux into the ocean interior is an important indicator of the BCP strength, and it can be directly measured by sediment traps on time scales from days to years. This study has been conducted in the South China Sea (SCS) for over three decades. The SCS is one of the largest tropical marginal seas, located in the Asian monsoon region with frequent occurrence of dynamic physical processes and anthropogenic perturbations. It hosts an ideal natural laboratory to investigate the response of the BCP to multiscale physical processes. In this mini review, we briefly introduce the study history of mooring sediment traps in the SCS, synthesize the processes that regulate the temporal variability in mesopelagic POC flux, and how it is sensitive to climate changes. The time-series characteristics of the POC flux are clearly linked to primary production, as well as the key physical processes in the upper layer. The seasonal East Asian monsoon, intraseasonal eddies, aerosol deposition and interannual El Niño Southern Oscillation (ENSO) events are the main controlling factors over weekly to yearly timescales. Together, they suggest that the multiscale physical forcing in the upper layer regulates the mesopelagic POC export flux by controlling nutrient supplementation and subsequent POC production.